TEACHER ACT IN CLASSROOM INTERACTION BASED ON SINCLAIR AND COULTHARD MODEL - Intan Permata Bunda; Siti Aisah Ginting; Isli Iriani Indiah Pane (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2020)
This study focused on teacher act in classroom interaction based on Sinclair and Coulthard Model. The aims of this study are (a) to find out the types of act in classroom interaction that the teacher used based on Sinclair and Coulthard Model, (b) to describe how the types of acts are realized in classroom interaction that the teacher used based on Sinclair and Coulthard Model. This research used qualitative research. To answer the problems of the study, the data were collected in two ways by observing, and recording. The data were analyzed based on Sinclair and Coulthard model. The results of this research were the following: (a) there were 16 types of acts in teacher utterances, namely:  Marker, Starter, Clue, Reply, Accept, Elicitation, Evaluate, Informative, Directive, React, Check, Conclusion, Comment, Cue, Bid, and Nomination. Meanwhile Prompt, Acknowledge, Metastatement, Loop, Silent stress, and Aside were not found during the teaching and learning process. (b) The realization of types of act Marker of act was realized by a closed class of item “Ok’’. Starter of act was realized by a command. Clue of act was realized by a statement. Reply act was realized by question. Accept of act was realized by a close of item “good’. Elicitation of act was realized by question. Evaluate of act was realized by statement and question tag. Informative of act was realized by a statement. Directive of act was realized by a command. React of act was realized by a non linguistic. Check of act was realized by statement. Conclusion of act was realized by a statement “so”. Comment of act was realized by a statement. Nomination of act was realized by a closed class consisting of the names of the pupil “please you”. Cue of act was realized by a close class of which “raise your hand”. Bid of act was realized by a close class of verbal items “Miss”.Keywords: Teacher Act, Classroom interaction, Act Sinclair and Coulthard.